2005
DOI: 10.1111/j.1572-0241.2005.40674.x
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Habit Subtypes and Temporal Patterns in Irritable Bowel Syndrome: Systematic Review

Abstract: IBS clinical subtypes distribution differs depending on the population evaluated, the geographical location, and the criteria employed to define IBS and bowel habit subtypes. In most cases, clinical course is characterized by the presence of mild-to-moderate symptoms appearing sequentially. Prospective studies, using clear and stable diagnostic criteria and subtype definitions, and based on daily data collection should further characterize IBS clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 38 publications
2
87
2
2
Order By: Relevance
“…The majority of previous studies have found a-IBS to be the most common subgroup, 29 especially when the investigation is primary care office-based. 26 We and others have demonstrated that the presence of diarrhoea is an explanation for referral from primary care to gastroenterologists, 30,31 which might explain higher proportion of d-IBS in some studies from gastroenterology offices. 32,33 In line with the majority of previous studies we found a-IBS to be the most common Rome II subgroup, whereas this was different with Rome III, where IBS-C and IBS-D were the most common subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previous studies have found a-IBS to be the most common subgroup, 29 especially when the investigation is primary care office-based. 26 We and others have demonstrated that the presence of diarrhoea is an explanation for referral from primary care to gastroenterologists, 30,31 which might explain higher proportion of d-IBS in some studies from gastroenterology offices. 32,33 In line with the majority of previous studies we found a-IBS to be the most common Rome II subgroup, whereas this was different with Rome III, where IBS-C and IBS-D were the most common subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for our divergent results between Rome II and Rome III subgrouping might relate to the fact that the patients only completed BSF diary cards during 1 week, as compared with the retrospective symptom recall for the previous 3 months. It is well-known that colonic function varies widely, not only in IBS patients, 15,25,26 but also in healthy subjects. 27 One might argue that completing the BSF diary cards for only 1 week is too short, but the optimal time period for this still needs to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to fluctuations over the medium (i.e., several months) or long (i.e., several years) term, a majority of patients randomized to placebo in therapeutic trials have rapidly fluctuating symptoms lasting from <1 h to <1 wk (11,12). We observed that stool frequency was more variable in women with functional GI disorders, but variation in stool frequency and form did not add to the utility of other features for discriminating functional bowel disorders from asymptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant lacuna, particularly in patients who have varying bowel habits, which is not uncommon in functional bowel disorders (7)(8)(9)(10). Indeed, studies from primary care and referral practices suggest that a majority of patients with irritable bowel syndrome (IBS) have symptoms of constipation and diarrhea, termed mixed IBS (or IBS-M) (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the relative proportions of IBS subtypes range from 5.2% to 66% for IBS-C, 0.8% to 33.9% for IBS-D, and 5.2% to 33.1% for IBS-A. 12 The chronic, episodic nature of IBS and CC and the limited sensitivity and specificity in diagnosis, as well as changes in diagnostic criteria over time, present substantial challenges for clinicians and researchers in characterizing the spectrum of patients' experiences.…”
mentioning
confidence: 99%